A importância da sobrevivência prolongada de neutrófilos nas zonas necróticas para o reparo tecidual e resolução da inflamação hepática - Matheus Silvério De Mattos (2021)
Acetaminophen (APAP) is a non-steroidal anti-inflammatory drug safe when used in therapeutical dosage. However, overdosage of this drug causes hepatocytes death by oncotic necrosis. APAP overdosage is the leading cause of acute liver failure in developed countries, contributing for millions of liver transplant cases. Hepatocytes death by necrosis culminates in the release of damage-associated molecular patterns into tissue, triggering inflammatory response and the consequent recruitment of neutrophils into the liver. Due its potential to cause collateral damage, neutrophil is classically perceived as an unstable cell, which are responsible to amplify APAP-induced liver injury. However, liver tissue repair is coincident with the maintenance of neutrophils at the inflammatory site during all stages of tissue repair. Objective: To evaluate neutrophil dynamics and transcriptional changes at liver, bone marrow and peripheral blood during all phases of APAP-induced liver injury and tissue repair, as well as to evaluate neutrophil behavior at necrotic sites, stressing out the potential role of neutrophils in resolution of inflammation and tissue repair. Experimental design: APAP-induced liver injury was performed by the administration of 600 mg/Kg of APAP, oral route, in female C57BL/6. We assessed neutrophil transcriptional changes, survival and its dynamics at necrotic liver, bone marrow and peripheral blood. Using intravital microscopy, we evaluated the neutrophil behavior within necrotic sites. Results and conclusion: We found that neutrophils remained viable during longer periods following liver damage, because they avidly patrolled necrotic areas and up-regulated proresolutive genes, including Tgfb, Il1r2, and Fpr2. Adoptive transference of resolutive neutrophils harvested from livers at 72 h after injury to mice at the initial phases of injury (6 h after APAP) significantly rescued organ injury. Thus, we provide novel insights on the role of neutrophils not only in the injury amplification, but also in the resolution phases of inflammation.